1992
DOI: 10.1002/bbpc.19920961122
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Electrostatic Potential and the Occupation of Interstitial Sites by Hydrogen in Metallic Systems

Abstract: The electrostatic crystal potentials V(r) of the cubic metals Pd, V, Nb, Ta, and the intermetallic phases FeTi and XEr, X = Cu, Ag, Au, have been determined by the full potential augmented‐plane‐wave method (FP‐APW). Furthermore, to study the electronic states in dilute metal‐hydrogen‐systems the partial densities of states have been calculated by the supercell procedure using the augmented‐spherical‐wave method (ASW) for PdH1/32. The results are compared with the values for PdH1/4, PdH, and Pd. – A relation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Much research on the Pd–H system has been carried out, mostly focused on the β phase (Pd hydride) so far . In the β phase, the electronic structure is quite different from that of the parent Pd because Pd−H bonding and antibonding states are formed in the Pd hydride.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Much research on the Pd–H system has been carried out, mostly focused on the β phase (Pd hydride) so far . In the β phase, the electronic structure is quite different from that of the parent Pd because Pd−H bonding and antibonding states are formed in the Pd hydride.…”
Section: Figurementioning
confidence: 99%
“…In the β phase, the electronic structure is quite different from that of the parent Pd because Pd−H bonding and antibonding states are formed in the Pd hydride. Such a change in the electronic structure by the hydride formation strongly influences the physical properties, which depend on the concentration of absorbed hydrogen, and has been well studied from both theoretical and experimental aspects . In contrast to the β phase, there has been no systematic study on the α phase, limited only to some fragmented researches, owing to the extremely low hydrogen concentration in the α phase compared with that in the β phase.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…18 Of the two previous studies, X␣ in general could be considered superior to EH (which is basically tight-binding). Philipp et al 13 found a correlation between the crystal electrostatic potential and the occupation of interstitial sites by H in bulk metals. They found that the t-site preference of H in bcc V, Nb, and Ta, and the o-site preference of H in fcc Pd could be correlated qualitatively with pure bulk metal's protonic electrostatic potential (i.e., the potential seen by a proton), which had its lowest value at the respective sites.…”
Section: B H In Bcc Fe: Site Preference and Dissolution Energymentioning
confidence: 99%
“…10 However, conflicting theoretical predictions of both site preferences and the direction of charge transfer have been reported. Geometrical factors, 11 lattice relaxations, 12 and electronic arguments 13 have been invoked to explain the site preference of H in bulk transition metals, though no universal theory can explain all cases.…”
Section: Introductionmentioning
confidence: 99%